Perceived Benefits of Learning Analytics and Artificial Intelligence-Based Oniline Learning Platforms: Case of Lithuanian General Education Schools - Aleksandra Batuchina; Julija Melnikova; Jelena Zascerinska; Andreas Ahrens (European Scientific Journal, ESJ, 2024)
Online learning platforms with integrated tools of learning analytics (LA) and artificial intelligence (AI) are growing in popularity in general education in Lithuania. Such platforms have a number of advantages in terms of the teaching-learning process, however, there is a lack of research about such advantages after direct use of the platforms in general education schools. Thus, the purpose of the current study is to find out the perceived benefits of online learning platforms with LA and AI tools. The research was conducted in 11 schools in Lithuania. The students at these schools tested the LearnLab and Eduten Playground online learning platforms for almost three months. Descriptive statistics methods and chi-square (χ2) criteria were applied. Results showed that students claim that their learning achievements have improved thanks to the platforms. Moreover, research results showed, that when working with platforms, it is appropriate to pay attention and, in parallel, to teach students computer literacy from the elementary grades, to develop a relationship with the computer as a work tool. It is also appropriate to start working with LA and AI platforms from the primary grades, which would positively stimulate the growth of digital competence, as well as the interest of students in the educational subject(s) and the positive growth of learning achievements.